Conjectures and theorems in the theory of entire functions - Csordas, G.; Dimitrov, D. K. (Baltzer Sci Publ Bv, 2000)
Motivated by the recent solution of Karlin's conjecture, properties of functions in the Laguerre-Polya class are investigated. The main result of this paper establishes new moment inequalities fur a class of entire functions represented by Fourier transforms. The paper concludes with several conjectures and open problems involving the Laguerre-Polya class and the Riemann xi -function.
Keywords: Laguerre-Polya class; Karlin's conjecture; Turan inequalities; double Turan inequalities; Fourier transform; admissible kernel; Riemann hypothesis; de Bruijn-Newman constant